PENGARUH PERENCANAAN SUKSESI DAN PELATIHAN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR PERUSAHAAN UMUM DAERAH AIR MINUM TUGU TIRTA KOTA MALANG - Iqbal Dwi Raharjo; Kristina Sedyastuti; Arien Anjar Puspitosari Suharso (ITB AAS Indonesia Surakarta, 2024)
This study examines the phenomena that arise in Human Resource Management. This study emphasizes the use of quantitative methods by involving 166 permanent employees in the Office of PERUMDA Tugu Tirta Malang City as research subjects. Proportional Random Sampling is used for sampling with Slovin formula. Data obtained by distributing questionnaires to employees. The independent variable consists of succession planning and job training, while the dependent variable is employee performance tested using multiple linear regression analysis. From the hypothesis testing conducted, it was found that succession planning and job training have a positive and significant effect simultaneously on employee performance. Partially succession planning has a significant and positive effect on employee performance, job training has an important and positive impact on employee performance. Suggestions for further researchers other variables outside of this study should be more widely studied that can affect employee performance. Keywords: Performance, succession planning, job training